(untitled) (Eurasian Research Bulletin, 2023)
The results of the research on 110 patients, treated in the Purulent Surgical Department of the Clinical Base of the Bukhara State Institute in 2010-2019, with lung abscesses with complications of bronchial fistula with various etiology were analyzed. According to the treatment method all patients were divided into 2 groups: I - comparison group and II – main group. The control of group I which consisted of 42 (38.2%) patients received traditional (conservative) methods of treatment. The main group which included 68 (61.8%) patients treated by conservative treatment and daily sanitation bronchoscopy with antibacterial and thinning drugs in the same time. The analysis of the obtained results revealed that the combined use of conservative therapy with sanitation bronchoscopy is a more effective method of treatment in comparison of conservative therapy without fibro-bronchoscopy